PENGARUH KOMPOSISI PULP NBKP DAN LBKP TERHADAP KUALITAS KERTAS ROKOK PADA PT BUKIT MURIA JAYA KARAWANG - Addin Akbar; Elsa Monika; Rizki Fadhillah Lubis; Demi Ramadian (Politeknik ATI Padang, 2019)
PT Bukit Muria Jaya is a company engaged in the manufacture of cigarette paper which has good quality paper, has a white color and low tear strength. The process of making cigarette paper carried out in PT Bukit Muria Jaya Laboratory has several stages of the process starting from taking raw materials in PM (paper machine) 1, mixing with starch, printing process, pressing process, and drying process. At the time of making cigarette paper using pulp of the NBKP and LBKP types. The shed paper that is made will be tested for the specified physical parameters such as grammature, tensile strength and permeability. In this research, cigarette paper will be made without using a CaCO3 filler with NBKP: LBKP variations are 35: 65, 45: 55, 55: 45, 65: 35, 75: 25, 85: 15, 95: 5%. The results showed that all variables used did not meet the desired physical properties of cigarette paper.